The Effect of Chemotherapy Treatment on Cognitive Impairment and Clinical Symptoms in Hodgkin Lymphoma Patients - Fayette, Dan; Juríčková, Veronika; Fajnerová, Iveta; Horáček, Jiří; Kozák, Tomáš (Cancers, 2025)
BACKGROUND/OBJECTIVES: Cancer- or chemotherapy-related cognitive deficit is a common side effect occurring in patients with Hodgkin lymphoma. No previous study compared the influence of different types of treatment on the onset and development of chemotherapy cognitive impairment in longitudinal design. The aim of this study was to assess whether a more intensive form of chemotherapy causes greater cognitive impairment. METHODS: Forty-four patients at three different stages of the disease and with three different treatments (ABVD + 30 Gy, BEACOPPesc, or ABVD + 30 Gy plus BEACOPPesc) completed the neuropsychological battery and psychological measures of affective distress and quality of life. We compared their cognitive performance before, immediately after, and 6 months after the treatment. RESULTS: Whether or not we divided the total number of people with Hodgkin lymphoma into two groups (mild and moderate disease versus severe disease) or three groups (mild, moderate, and advanced disease), we found no statistically significant difference between the groups in cognitive performance or other psychological factors or experienced quality of life. CONCLUSIONS: Our results did not show that disease stage or treatment protocol had an effect on the depth of cognitive impairment in cancer or chemotherapy. We hypothesize that, in terms of brain health, intensive forms of chemotherapy (6 × BEA-COPPesc) do not pose a greater risk than milder forms (4 × ABVD + 30 Gy IF RT and 2 × BEACOPPesc + 4 × ABVD + 30 Gy IF RT) of cancer treatment for Hodgkin lymphoma. However, a limitation of our study is the small number of participants in the study, so it would be advisable to repeat the study on a larger sample of patients. Confirmation of our results could be beneficial in that neither patients nor physicians need to worry that intensive chemotherapy will worsen cognitive deficits.
Keywords: chemotherapy; Hodgkin lymphoma; chemotherapy-related cognitive impairment; cancer-related cognitive impairment; cancer; cognitive functions